Synopsis: Grain storage and marketplace characteristics in Kebbi state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George; Maikasuwa, Mohammed Abubakar; Aliyu, Abdulrahaman; Bashir, Amina (International Food Policy Research Institute, 2018)
The focus of this study is on the physical infrastructure of marketplaces in Kebbi state, Nigeria, an agriculture-based state in the northwest. Kebbi state has distinct variation in climate within a crop year, and, hence, there is need for farmers and traders to store produced crops for use during the year. Increased investments in storage facilities in the state could accelerate agricultural development.